Evapotranspiration of full-, deficit-irrigated and dryland cotton on the northern Texas High Plains - Howell, T. A., author; Evett, S. R., author; Tolk, J. A., author; Schneider, A. D., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
Cotton (Gossypium hirsutum L.) is beginning to be produced on the Northern Texas High Plains as a lower water-requiring crop while producing an acceptable profit. Cotton is a warm season, perennial species produced like an annual yet it requires a delicate balance of water and water deficit controls to most effectively produce high yields in this thermally limited environment. This study measured the water use of cotton in near-fully irrigated, deficiently irrigated, and dryland regimes in a Northern Texas High Plains environment, which has a shortened cotton producing season, using precision weighing lysimeters in 2000 and 2001. The irrigated regimes were irrigated with a lateral-move sprinkler system. The water use data were used to develop crop coefficient data and compared with the FAO-56 method for estimating crop water use. Cotton yield, water use, and water use efficiency was found to be as good in this region as other more noted cotton regions. FAO-56 ET prediction procedures performed better for the more fully irrigated treatments in this environment.
USCID/EWRI conference
Northern Texas High Plains
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.